Prevalence of partial and total edentulism in Butachauques and Tac Islands, Quemchi, (Chile) 2013 - Cortés, Víctor; Carrasco, Felipe; Vergara, Carolina (Revista Chilena de Salud Pública, 2014)
Aim: To determine the prevalence of edentulism and Kennedy topographic classification in the population aged over 20 years of the Butachauques and Tac islands, Quemchi, Chile. Materials and Methods: Descriptive study. We included subjects aged over 20 years at health services of the Butachauques and Tac islands during the months of August and September 2013. Subjects were asked to sign an informed consent form. The information collected was entered into a data entry form. The variables used were gender, age, number of teeth present, and type of prosthesis and edentulous type according to Kennedy’s topographic classification. Descriptive statistics were determined using SPSS 18 (IBM® SPSS® software) statistical software. Results: 88 subjects, 39.7% men and 60.3% women, were evaluated. 89.7 % of the subjects had absence of at least one of their teeth and 29.4% of these were using dentures. The most prevalent maxillary classification was Class 3, while the mandibular arch had similar results for class 1 and 3. Conclusion: These results demonstrate a high prevalence of edentulous subjects in the various health services of the islands, and the need for promotion and prevention programs to minimize damage to the health of people in these localities.